1967
DOI: 10.1542/peds.40.4.596
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Characteristics of Abused Children

Abstract: The account of these patients documents the necessity for critical attention to the entire environment, including cultural factors believed to be especially important in the care and development of the injured child. It further documents the necessity for early intervention when abuse is suspected. Drastic management by removal from the home, the only method of intervention referred to in this paper, is indicated when the caretaker cannot respond to milder measures designed to improve his relations with the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1971
1971
1986
1986

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Thus this perception may persist after the initially aversive characteristics have been outgrown. This would help account for the fact that prematurely born children are more likely to be abused than those born at term (Elmer & Gregg, 1967;Fontana, 1973;Klein & Stern, 1971;Simons et al, 1966).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus this perception may persist after the initially aversive characteristics have been outgrown. This would help account for the fact that prematurely born children are more likely to be abused than those born at term (Elmer & Gregg, 1967;Fontana, 1973;Klein & Stern, 1971;Simons et al, 1966).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that infant cries may serve to elicit child abuse suggested that one reason for the frequency with which premature infants are abused (see Elmer & Gregg, 1967;Fontana, 1973;Klein & Stern, 1971;Simons, Downs, Hurster, & Archer, 1966) might be that their cries are especially aversive. In addition, since premature infants not only sound different but also look different (even to untrained lay persons), we reasoned that their facial configuration might be such that they proved less effective elicitors of the "cute" response (Jolly, 1972;Lorenz, 1935Lorenz, /1970, and might in fact be perceived as aversive.…”
mentioning
confidence: 99%
“…In addition, the behavior patterns of abused children closely resembled the range of behavior problems shown by children from distressed families in which abuse was not present. The implications of these results for understanding and helping abused children and their parents are discussed.Early clinical reports of abused children noted a greater rate of child abuse among children with physical and general developmental deviations than among normal comparison children (Elmer & Gregg, 1967;Gil, 1968;Johnson & Morse, 1968). For example, premature and low-birth-weight children are believed to be especially at risk for abuse due, in part, to the extra childrearing burden placed on parents by children with special needs (Elmer & Gregg, 1967;Skinner & Castle, 1969).…”
mentioning
confidence: 99%
“…The implications of these results for understanding and helping abused children and their parents are discussed.Early clinical reports of abused children noted a greater rate of child abuse among children with physical and general developmental deviations than among normal comparison children (Elmer & Gregg, 1967;Gil, 1968;Johnson & Morse, 1968). For example, premature and low-birth-weight children are believed to be especially at risk for abuse due, in part, to the extra childrearing burden placed on parents by children with special needs (Elmer & Gregg, 1967;Skinner & Castle, 1969). These findings led investigators to reconceptualize child abusive behavior in terms of aversive interactions between parents and children, rather than adult psychopathology alone (…”
mentioning
confidence: 99%
“…It has been claimed that many abused children have difficulties in school-related tasks (Martin, 1972(Martin, ,1976Blager & Martin, 1976;Martin & Rodeheffer, 1976a, 1976bKline, 1977;Christiansen, 1980;Frisch & Rhoads, 1982;Friedrich, Einbender, & Luecke, 1983). A high incidence of mental retardation has been reported among abused children (e.g., Elmer & Gregg, 1967;Martin, 1972;Gil, 1970), but the nature of the cause-effect relationship(s) between mental retardation and abuse…”
mentioning
confidence: 99%